Menelisik Ayat-Ayat Gempa Pada Hari Kiamat (Analisis Tafsīr Al-Jawāhir Fi Tafsīr Al-Qurān Al-Karim karya Tantawi Jauhari) - Uun Yusufa; Umi Wasilatul Firdausiyah (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2021)
The discourse of this research relates to the earthquake verses on the Day of Judgment, by looking at the interpretation of Tantawi Jauhari on the interpretation of Qs. Al-Hajj verse 1 and Qs. Al-Zalzalah verse 1 on the word Zalzalah (earthquake), Qs. Al-Waqiah verse 4 on the word Rajj (great shaking), Qs. Al-Hāqah verse 14 on the words Dakk (the earth collides, the earth shakes), Qs. Al-Nazi'at verse 6 on the word Rajfah (great earthquake), with his interpretation, tries to contextualize the text with the current conditions by using a scientific interpretation approach. So that it raises positive implications that are axiological or applicable that the verses of the Qur'an have continuity in providing instructions for humans which are packaged in a relevant language. And also negative implications, which lead to misunderstandings regarding the verses of mubham, muhkam, and mutasyabihat; it is as if the Qur'an came down in relation to events that are happening, even though not all of the verses are like that; and the religious values of the Koran are reduced.